(untitled) (Research, Society and Development, 2020)
Objective: To report the experiences of educational actions lived during activities of extension about breastfeeding and breastfeeding carried out in a Maternity s. In addition to highlighting the importance of breastfeeding and its correct techniques. Methods: This is a descriptive study, of the experience report type obtained from the experiences of an extension project carried out with puerperal women in the period from November 2019 to February 2020, in a maternity hospital located in a municipality in the interior of Maranhão. Results: During the period of activities, the mothers were instructed about the importance of breastfeeding and correct techniques so that it could occur in a safe and pleasant way. Conclusion: It is necessary that the woman is safe and well informed about the correct management of breastfeeding. Thus, all the benefits that breastfeeding provides for both mother and baby can be achieved.